Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index - Speliotes, E; Willer, C; Berndt, S; Monda, K; Thorleifsson, G; Jackson, A; Allen, H; Lindgren, C; Luan, J; Maegi, R; Randall, J; Vedantam, S; et al. (2010)
Obesity is globaLy prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined aSociations betwEn body maS index and ĝ̂1/42.8 miLion SNPs in up to 123,865 individuals with targeted foLow up of 42 SNPs in up to 125,931 aDitional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci aSociated with body maS index (P < 5-10-8), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly aSociated loci may provide new insights into human body weight regulation. © 2010 Nature America, Inc. All rights reserved.